Level of acceptance of news stories on social media platforms among youth in Nigeria - Olise, Festus Prosper (Penerbit Universiti Kebangsaan Malaysia, 2021)
This study investigates the level of acceptance of news stories on social media platforms among youth in Nigeria following the assumption that the proliferation of news stories on social media promotes the circulation of both factual and fake news. The sample consisted of 600 youth; however, 583 validly participated in the study. The participants were equitably selected in six States in Nigeria that represented the six geo-political zones of the country. The multi-stage sampling technique was employed to evenly select the youth from the major cities/towns in the States. Data generated were analysed and presented through descriptive and inferential statistics using SPSS version 20 software. Results show that the youth accepted entertainment news stories more than any other type of news stories on social media platforms. The majority of the youth considered Twitter as the most acceptable social media platform for receiving news stories in Nigeria. Findings also revealed that despite their love to read news stories on social media platforms, the youth’s level of acceptance of it was low. Furthermore, the age and gender of the youth were found to directly influence their level of acceptance of news stories on social media platforms. The study concluded that the multi-dimensional inter-play that characterised the low level of acceptance of news stories on social media platforms among the youth in Nigeria does not portend ominous signs.